Effect of polyunsaturated fatty acids on the reactive oxygen and nitrogen species production by raw 264.7 macrophages - Ambrozova, Gabriela; Pekarova, Michaela; Lojek, Antonin (European journal of nutrition, 2010)
BACKGROUND: Polyunsaturated fatty acids (PUFAs) can affect various functions of the immune system including inflammatory responses. An oxidative burst of phagocytes accompanied by reactive oxygen species (ROS) and reactive nitrogen species (RNS) formation is one of the phagocyte functions that could be modulated by PUFAs. AIM OF THE STUDY: To investigate the effects of omega-3 (alpha-linolenic, docosahexaenoic, eicosapentaenoic) and omega-6 (arachidonic, linoleic) PUFAs on lipopolysaccharide (LPS)-stimulated ROS and RNS production by the murine macrophage cell line RAW 264.7. METHODS: Murine peritoneal macrophages RAW 264.7 were stimulated with LPS (0.1 microg/ml) and treated with 0.1-100 microM omega-3 or omega-6 PUFAs for either 8 (ROS production) or 20 h (RNS production). The cytotoxicity of PUFAs was evaluated by an ATP (adenosine triphosphate) test after both 8 and 20 h of treatment with PUFAs. Changes in ROS production by LPS-treated macrophages subsequently activated with phorbol myristate acetate (PMA) or opsonized zymosan particles (OZP) were determined by luminol-enhanced chemiluminescence, whilst the production of RNS was determined as the concentration of nitrites in cell supernatants (Griess reaction). Changes in inducible nitric oxide synthase (iNOS) expression were evaluated by Western blot analysis. The antioxidant properties of PUFAs were tested by TRAP (total peroxyl radical-trapping antioxidant parameter) assay. RESULTS: All PUFAs in 100 microM concentration except eicosapentaenoic acid decreased ROS production. The effect was most significant when docosahexaenoic acid was used. Arachidonic acid decreased PMA-activated ROS production even in 1 and 10 microM concentrations. On the other hand, 10 and 100 microM eicosapentaenoic acid potentiated ROS production. As concerns RNS production, all the fatty acids that were tested in a concentration of 100 microM decreased iNOS expression and nitrite accumulation. Fatty acids had no significant effect on the viability and proliferation of RAW 264.7 cells. The TRAP assay confirmed that none of the tested PUFAs exerted any significant antioxidant properties. CONCLUSION: High concentrations of PUFAs of both omega-3 and omega-6 groups can inhibit ROS and RNS formation by stimulated macrophages. The expression of iNOS can also be inhibited. This effect, together with the absence of antioxidant activity and cytotoxic properties, indicates that PUFAs can participate in the regulation of enzymes responsible for reactive species production.
Keywords: Cell Survival; Electrophoresis, Polyacrylamide Gel; luminiscenční měření; Oxidative Stress; reaktivní formy kyslíku; Luminescent Measurements; oxidační stres; Fatty Acids, Unsaturated; Nitrogen; elektroforéza v polyakrylamidovém gelu; dusík; nenasycené mastné kyseliny; Nitrites; makrofágy; Blotting, Western; synthasa oxidu dusnatého; zvířata; Cells, Cultured; myši; Nitric Oxide Synthase; dusitany; Reactive Oxygen Species; časové faktory; Mice; kultivované buňky; Animals; Macrophages; western blotting; Time Factors; viabilita buněk